Photocatalytic degradation and heat reflectance recovery of waterborne acrylic polymer/ZnO nanocomposite coating. Issue 37 (13th February 2020) - Nguyen, Thien Vuong; Dao, Phi Hung; Nguyen, Tuan Anh; Dang, Viet Hung; Ha, Minh Nguyet; Nguyen, Thi Thuy Trang; Vu, Quoc Trung; Nguyen, Ngọc Linh; Dang, Tran Chien; Nguyen‐Tri, Phuong; Tran, Dai Lam; Lu, Le Trong
Abstract: This work aims to clarify the photocatalytic degradation mechanism and heat reflectance recovery performance of waterborne acrylic polymer/ZnO nanocomposite coating. To fabricate the nanocomposite coating, ZnO nanoparticles (nano‐ZnO) were dispersed into acrylic polymer matrix at the various concentrations from 1 to 6% (by total weight of resin solids). The photocatalytic degradation of nanocomposite coating under ultraviolet (UV) light irradiation has been investigated by monitoring its weight loss and chemical/microstructural/morphological changes. As the topcoat layer, its heat reflectance recovery has been evaluated under UV/condensation exposure by using an artificial dirty mixture of 85 wt% nanoclay, 10 wt% silica particles (1–5 μm), 1 wt% carbon black, and 2 wt% engine oil. After 108‐cycle UV/condensation exposure, infrared spectra and weight loss analysis indicated that the maximal degradation for nanocomposite coating is observed at 1 wt% nano‐ZnO. On the other hand, after 96 hr of UV light exposure, the nanocomposite coating with1 wt% nano‐ZnO could restore effectively the reflective index of solar‐heat reflectance coating (from 58.45 to 80.78%). Finally, the photodegradation mechanism of this waterborne acrylic polymer coating has been proposed as the UV‐induced formation of CCCO conjugated double bonds. As a result, its self‐cleaning phenomenon can be achieved as the recovery of heat reflectance. Abstract :